Aristotle’s De Anima as Source of Aquinas’ Anthropological Doctrine - Lukac de Stier, María L. (Philosophia, 2019)
The aim of this paper is to highlight some basic issues in Aquinas’ anthropology, as they appear in the Commentary on Aristotle’s De Anima. To do this, in the special case of the possible intellect, we will confront other original works of Aquinas’ where, even when his thought is more freely reflected, the Aristotelian origin of the works is evident.